Fuzzy Logic Implementation with MATLAB for PV-Wind Hybrid System - Alias Khamis; Mohd Ruddin Ab. Ghani; Chin Kim Gan; Mohd Shahrieel Mohd Aras; Muhamad Fiqry Khamis; Tole Sutikno; Jano Zanariah (Universitas Ahmad Dahlan, 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexThe development of hybrid renewable energy sources is vital in power generation. This study focused on design of fuzzy logic control on hybrid PV/Wind system in order to improve the speed of DC motor. The fuzzy logic control based on battery management system has been designed for effective power utilization and improvement of the DC motor speed performance. In battery management system, a control was proposed to operate the charging and discharging mode of battery during non-linear power generation. While the battery would charge whenever the renewable energy power was greater than consumer load power, the battery would discharge whenever the renewable energy power was less than the consumer load power. DC motor speed control, included the simulation, implementation of fuzzy logic controller to DC motor and comparison between PID controller and Fuzzy Logic Controller. The proposed model was simulated using Matlab environment and the results was analyzed. Finally, simulation results were evaluated and validated to determine the effectiveness of the proposed controller.